2019
DOI: 10.3126/njn.v16i3.27360
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Neurological Diseases in Tertiary Care Centre of Nepal

Abstract: Neurological cases in Nepal are not reported much. Neurological diseases are associated to poor health outcomes including mortality, disability and hospitalization. Epidemiology and clinical pattern of neurological disorders in developing countries remain largely unknown. This is a descriptive study to understand the burden of disease faced by neurologists and internists in a hospital of Nepal. This is a retrospective study of medical records of patients admitted in the Neurology unit of medical ward of Dhulik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The present study has shown that cerebrovascular disease was the most common reason for admission of patients in the ICU which is similar to other studies. [18][19][20] This may be because the cerebrovascular disease is an emergency requiring ICU care while other diseases may present as a non-emergency condition.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has shown that cerebrovascular disease was the most common reason for admission of patients in the ICU which is similar to other studies. [18][19][20] This may be because the cerebrovascular disease is an emergency requiring ICU care while other diseases may present as a non-emergency condition.…”
Section: Discussionmentioning
confidence: 99%
“…More and more children are seeking well facilitated neuro centers every day. 3 In our hospital, being only one tertiary center for child care, most of the children from Nepal is being referred. People from different parts of Nepal are visiting here as super specialty service is very limited.…”
mentioning
confidence: 99%